Aesop's fables - Aesop; Ash, Russell, 1946-2010.; Higton, Bernard (San Francisco : Chronicle Books, 1990)
Although he was probably as mythical as the tales attributed to him, the legendary name of Aesop has been associated for thousands of years with an enduringly popular collection of enchanting fables. This delightful selection of Aesop's parables--some universally recognizable, others refreshingly unfamiliar--is magnificently complemented by illustrations taken from a variety of antique editions of the fables. Among the artists represented in this beautifully reproduced new volume are Arthur Rackham, Thomas Bewick, Walter Crane, Charles Robinson, and Randolph Caldecott. This stunning compemdium includes fully captioned illustrations, a complete bibliography of sources, and a set of biographical notes on the artists.-- Publisher.
Aesop and his illustrators. -- The fables: The hare and the tortoise -- The frog and the ox -- The wolf and the crane -- The mice in council -- The lion in love -- The peacock's complaint -- The cock and the fox -- The bear and the bees -- The vain jackdaw -- The wind and the sun -- The trees and the axe -- The lion and other beasts -- The man and his two wives -- The town mouse and the country mouse -- The fox and the stork -- The lion and the mouse -- The old woman and her maids -- The ass and the little dog -- The two playmates -- The cat, the cock and the young mouse -- The wolf and the ass -- The ants and the grasshopper -- Venus and the cat -- The mountain in labour -- The fox and the lion -- The cat and the cock -- The bear and the fox -- The dog in the manger -- The young man and the fickle woman -- The fox and the crow -- The man, his son and the ass -- The wolf and the goat -- The piping fisherman -- The boys and the frogs -- The fox and the grapes -- The ass in the lion's skin -- The dog and his shadow -- The fox and the mask -- The eagle and the arrow -- The cock and the jewel -- The frogs desiring a king -- The goose that laid the golden eggs -- The monkey and the dolphin -- The travellers and the bear -- The thieves and the cock -- The astronomer -- The ass and his driver -- The rose and the butterfly -- The boy who cried wolf -- The kite, the hawk and the pigeons -- The hares, the foxes and the eagles -- The lion and the gnat -- The leopard and the fox.
Includes bibliographical references (page 94).
Keywords: Fables, Greek -- Translations into English; Fables; Folklore; Fables, Greek; Translations; Fables